Changing Embodied Dialogical Patterns in Metacognitive Interpersonal Therapy. Issue 2 (3rd April 2021) - Centonze, Antonella; Inchausti, Felix; MacBeth, Angus; Dimaggio, Giancarlo
Abstract: According to proponents of Dialogical Self Theory (DST), the self is made up of a series of I-positions, which continuously interact, negotiating potential courses of action, and attributing meaning to events. Individuals with personality disorders tend to attribute meaning according to stereotyped dialogical relationship patterns which prevent them from achieving social adaptation and fulfillment. Of note, in our perspective, we do not necessarily take dialogical relationship as healthy. We refer to dialogical thinking as a form of thoughts about interpersonal interactions, but the very dialogue may itself be stuck and repetitive as in the case of patients with personality disorders (Dimaggio et al., 2003, 2010 ; Schacter et al., 2012). These patterns do not just take the form of verbal discourse, but are instead embodied and rooted within internalized processes; which are themselves laden with affect, behavioral dispositions and somatic experiences. Using a case study we demonstrate how Metacognitive Interpersonal Therapy (MIT) provides a platform for changing embodied dialogical patterns, via imagery and body work. These techniques enable revision of the embodied component of the dialogical pattern, promoting the emergence of new I-positions. These new patterns comprise more adaptive aspects and correspondingly impede the enactment of previous maladaptive coping strategies, that were driven by pathological I-positions. Finally, we discuss the implications of experiential work in this context, as a crucial component of dialogical oriented therapies for people experiencing severe interpersonal problems such as personality disorders.